Compression behavior of FRP strengthened bridge timber piles subjected to accelerated aging. (15th October 2016) - Kim, Kun-Ho Eugene; Andrawes, Bassem
Highlights: Field extracted timber pile specimens were retrofitted with FRP composites. An accelerated aging protocol was used to simulate long-term degradation. Compressive behavior of specimens is compared with and without accelerated aging. FRP wrapping greatly improves strength and ductility even with accelerated aging. Abstract: The use of fiber reinforced polymer (FRP) composites has been identified an effective way to strengthen and protect timber piles in many different applications. This experimental study focuses on examining the performance of glass-FRP (GFRP) strengthened bridge timber piles under uniaxial compression after exposure to long-term degradation. Field extracted red oak pile specimens with different degrees of initial deterioration are used in the study. The initial condition of the timber is assessed through stress wave timing. In order to simulate natural degradation in unretrofitted and retrofitted timber piles due to environmental exposure in a short period of time an accelerated aging procedure is used. In total, 24 timber pile specimens are tested in uniaxial compression. The number of FRP layers and type of resin used (polyester, standard epoxy, and moisture tolerant epoxy) are varied. Results show that accelerated aging induces significant deterioration in unretrofitted timber piles but the effects are relatively minor in the FRP wrapped specimens. It is also proven that FRP composite is able to significantly improve the performance of timber piles in terms of peak stress and ductility even after being subjected to extreme degradation.